High permeability flexible gas sealing material and preparation method thereof

By using lime, magnesium oxide, polyester compounds and composite resins, the problem of insufficient stability and corrosion resistance of existing materials is solved, and effective sealing and long-term under complex geological conditions are achieved Stable performance.

CN118725835BActive Publication Date: 2025-01-10HEBEI ZHIRUI NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411230004.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-01-10
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

The stability, corrosion resistance and toughness of existing gas sealing materials are poor, making it difficult to meet the requirements of drilling sealing under complex geological conditions, affecting the gas extraction effect.

Method used

Using a high permeability flexible gas sealing material composed of lime, magnesium oxide, polyester compounds and composite resins, polyester compounds and composite resins are prepared by specific synthetic methods to form a seal with excellent stability, corrosion resistance and flexibility. Pore ​​material.

Benefits of technology

It improves the stability, corrosion resistance and toughness of the sealing material, ensures uniform distribution in complex pore structures, extends service life, and maintains the performance unchanged in gas environments, improving impact resistance and fatigue resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-permeability flexible gas sealing material and a preparation method thereof, and belongs to the technical field of sealing material preparation. The high-permeability flexible gas sealing material is composed of the following components in parts by weight: 20-30 parts of lime, 10-12 parts of magnesium oxide, 18-22 parts of polyester compounds, 20-28 parts of composite resins, 2-5 parts of stabilizers, and 1-4 parts of silane coupling agents, wherein the polyester compound is prepared from 2-methyl-2-propyl-1,3-propylene glycol, 2,4-dihydroxy-3,3-dimethylbutyric acid and acrylic acid, and the composite resin is prepared from 1,1,1-tri-p-hydroxyphenylethane, 5-norbornene-2-methylamine and 2,3-dihydrofuran. The gas sealing material prepared by the method has excellent stability, corrosion resistance and flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flexible gas sealing material preparation, and in particular relates to a high-permeability flexible gas sealing material and a preparation method thereof. Background Art

[0002] As the depth of coal mining continues to increase, the geological conditions of coal seams are becoming increasingly complex, and gas disasters are frequent, which seriously threaten the safe production of mines. As the main means of preventing gas outbursts and gas accidents, the effect of gas extraction is directly affected by the quality of borehole sealing.

[0003] Traditional gas extraction borehole sealing materials, such as cement mortar, have shortcomings such as poor sealing quality, low permeability, insufficient material strength, and long consolidation time. It is difficult to effectively seal the cracks around the borehole, resulting in gas leakage and affecting the extraction effect. In addition, traditional materials are often unable to cope with borehole sealing under complex geological conditions and cannot meet the needs of modern coal mine safety production.

[0004] Patent CN 113248197 B discloses a waste incineration fly ash-based flexible gas sealing material and a preparation method thereof. The waste incineration fly ash-based flexible gas sealing material in the method comprises the following raw materials: 40-60 parts of domestic waste incineration fly ash, 5-10 parts of domestic waste incineration low ash, 33-45 parts of Portland cement, 16-23 parts of pure acrylic emulsion or chloroprene latex, 0.8-1.5 parts of medical waste incineration fly ash, 4-6 parts of water-based epoxy resin, 2-3 parts of water-based epoxy curing agent, 0.5-2 parts of sodium hydroxide or potassium hydroxide, 0.01-0.03 parts of triethanolamine, 0.05-0.2 parts of polyacrylamide or 0.5-1 parts of dodecyl dimethyl amine oxide, 3-5 parts of glass fiber and 34-44 parts of water. The sealing material in this invention can adapt well to drilling deformation and ensure the sealing density. It also does not produce serious metal pollution under long-term immersion in acidic mine water, thus realizing resource utilization. However, the stability, corrosion resistance and toughness of the sealing material prepared by this invention still have room for improvement. Summary of the invention

[0005] The object of the present invention is to provide a high-permeability flexible gas sealing material and a preparation method thereof, so as to solve the technical problems of poor stability, corrosion resistance and toughness of the sealing material in the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The invention provides a high-permeability flexible gas sealing material, which is composed of the following components in parts by weight: 20-30 parts of lime, 10-12 parts of magnesium oxide, 18-22 parts of polyester compounds, 20-28 parts of composite resins, 2-5 parts of stabilizers, and 1-4 parts of silane coupling agents, wherein the polyester compound is prepared from 2-methyl-2-propyl-1,3-propanediol, 2,4-dihydroxy-3,3-dimethylbutyric acid and acrylic acid, and the composite resin is prepared from 1,1,1-tri-p-hydroxyphenylethane, 5-norbornene-2-methylamine and 2,3-dihydrofuran.

[0008] Preferably, the method for preparing the polyester compound comprises the following steps:

[0009] Q1: 2-methyl-2-propyl-1,3-propanediol and 2,4-dihydroxy-3,3-dimethylbutyric acid are mixed and added to a container, heated and mixed until molten, and then p-toluenesulfonic acid and di-tert-butyl-4-methylphenol are added, and the temperature is raised and stirred to react. After the reaction is completed, the heating is stopped and the temperature is lowered to obtain an intermediate product 1;

[0010] Q2: Add intermediate product 1 to a container, then add toluene, p-toluenesulfonic acid and hydroquinone, stir evenly, add acrylic acid, heat and react, and after the reaction is completed, obtain intermediate product 2;

[0011] Q3: The intermediate product 2 is mixed with propionic acid, heated and stirred for reaction, and after the reaction is completed, vacuum is applied, the mixture is cooled, and then 4-methoxyphenol is added, and the mixture is stirred and mixed to obtain a polyester compound.

[0012] In the above process, the synthesis reaction formula of the polyester compound is as follows:

[0013]

[0014] The results of mass spectrometry analysis were: m / z: 1348.61 (100.0%), 1349.61 (73.5%), 1350.62(27.5%), 1351.62 (10.9%), 1350.61 (5.8%), 1352.62 (2.8%), 1349.62 (1.1%).

[0015] Preferably, in Q1, the molar ratio of 2-methyl-2-propyl-1,3-propanediol to 2,4-dihydroxy-3,3-dimethylbutyric acid is (1-2): (6-12), the container contains a mechanical stirrer and a thermometer, the heating and mixing temperature is 130-135°C, the heating and stirring reaction temperature is 120-130°C, inert gas is used for protection during the stirring reaction and a water separator is used, and the reaction time is 2-4h; in Q2, the molar ratio of the intermediate product 1 to acrylic acid is (1-1.5): (6-9), the stirring time is 1-2h, the heating and reaction temperature is 120-130°C, and the reaction time is 6-8h; in Q3, the molar ratio of the intermediate product 2 to propionic acid is (1-2): (2-4), the heating and stirring temperature is 120-130°C, the reaction time is 1-2h, the temperature is cooled to 90-95°C, and the stirring and mixing time is 20-30min.

[0016] Preferably, the method for preparing the composite resin comprises the following steps:

[0017] S1: Add paraformaldehyde and toluene into a container, heat and stir in an oil bath, then add 1,1,1-tri-p-hydroxyphenylethane, continue stirring, then add 5-norbornene-2-methylamine into the container, heat and stir to react, after the reaction is completed, wash, rotary evaporate, and vacuum dry to obtain intermediate product A;

[0018] S2: Add [1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinyl]dichloro(phenylmethylene)bis(3-bromopyridinium)ruthenium into a container containing dichloromethane, stir to dissolve, evacuate, and pass nitrogen to obtain a catalyst solution;

[0019] S3: The intermediate product A is added to dichloromethane, followed by 2,3-dihydrofuran, and ultrasonically mixed to obtain a mixed solution, which is added to the catalyst solution via a syringe. After heating and stirring, ethyl vinyl ether is added to terminate the reaction, and stirring is continued. Subsequently, precipitation, dissolution-precipitation operations are repeated, and vacuum drying is performed to obtain a composite resin.

[0020] In the above process, the synthetic reaction formula of the composite resin is as follows:

[0021]

[0022] Preferably, in S1, the molar ratio of paraformaldehyde, 1,1,1-tri-p-hydroxyphenylethane and 5-norbornene-2-methylamine is (1-2): (3-6): (9-18), the oil bath heating temperature is 40-45°C, the stirring time is 30-45min, the continued stirring time is 30-45min, the heating and stirring reaction temperature is 70-80°C, the stirring reaction time is 12-15h, and the mixture is first washed with 1mol / L NaOH solution and then washed with deionized water until neutral.

[0023] Preferably, in S2, the dosage ratio of [1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinyl]dichloro(phenylmethylene)bis(3-bromopyridine)ruthenium and dichloromethane is (0.004-0.008) g: (2-4) mL, and the stirring time is 30-45 min.

[0024] Preferably, in S3, the usage ratio of the intermediate product A, 2,3-dihydrofuran and vinyl ethyl ether is (3.5-7) g: (0.62-1.24) g: (0.5-1) mL, the heating and stirring temperature is 40-50°C, the stirring time is 2-4h, the continued stirring time is 10-15min, and the vacuum drying temperature is 50-60°C, and the time is 20-24h.

[0025] Preferably, the stabilizer is obtained by mixing methyl stearate and polyvinyl alcohol aqueous solution, wherein the mass fraction of the polyvinyl alcohol aqueous solution is 5wt%-10wt%, and the dosage ratio of methyl stearate to polyvinyl alcohol aqueous solution is (8-10) g: (10-15) mL.

[0026] Preferably, the method for preparing the high permeability flexible gas sealing material comprises the following steps:

[0027] Step (1): mixing and stirring lime, magnesium oxide, polyester compound, composite resin and silane coupling agent to obtain a sealing material premix;

[0028] Step (2): Mix and stir the sealing material premix and the stabilizer to obtain a high-permeability flexible gas sealing material.

[0029] Preferably, in step (1), the mixing and stirring time is 30-45 min; in step (2), the mixing and stirring time is 30-45 min.

[0030] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0031] 1. The present invention first uses 2-methyl-2-propyl-1,3-propanediol, 2,4-dihydroxy-3,3-dimethylbutyric acid, acrylic acid and propionic acid as raw materials to prepare a polyester compound, and then uses polyformaldehyde, 1,1,1-tri-p-hydroxyphenylethane, 5-norbornene-2-methylamine and 2,3-dihydrofuran as raw materials to prepare a composite resin. The polyester compound and the composite resin are used as the main raw materials of the sealing material, so that the sealing material has excellent stability, corrosion resistance and flexibility.

[0032] The present invention uses 2-methyl-2-propyl-1,3-propanediol as a central core and 2,4-dihydroxy-3,3-dimethylbutyric acid as a monomer to prepare an intermediate product 1, and then obtains an intermediate product 2 by esterification reaction between the intermediate product 1 and acrylic acid. Subsequently, the remaining hydroxyl groups are capped with propionic acid to obtain a polyester compound with low viscosity. The polyester compound is used as the main raw material of a sealing material, so that the prepared sealing material can better adapt to complex pore structures, ensure uniform distribution, and reduce the problem of incomplete sealing caused by poor material fluidity; and the polyester compound has excellent toughness, chemical stability and thermal stability, so that the sealing material can maintain unchanged performance in a gas environment, thereby extending the service life of the sealing material.

[0033] The present invention uses 1,1,1-tri-p-hydroxyphenylethane, 5-norbornene-2-methylamine and polyformaldehyde as raw materials to obtain an intermediate product A, and then reacts the intermediate product A with 2,3-dihydrofuran through a ring-opening metathesis polymerization reaction to prepare a composite resin. The composite resin is used as the main raw material of a sealing material to effectively improve the corrosion resistance and stability of the sealing material. The highly cross-linked network structure formed in the composite resin enables the sealing material to have excellent resistance to various corrosive media, so that the sealing material can maintain its structural integrity and stable performance when exposed to a corrosive environment; at the same time, the network structure enables the sealing material to evenly disperse stress when subjected to an external force, thereby improving its impact resistance and fatigue resistance. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] This embodiment discloses a method for preparing a polyester compound, comprising the following steps:

[0037] Q1: 0.75 g of 2-methyl-2-propyl-1,3-propanediol and 5.54 g of 2,4-dihydroxy-3,3-dimethylbutyric acid were mixed and added to a container containing a mechanical stirrer and a thermometer, and mixed at 125°C until molten, followed by adding 0.31 g of p-toluenesulfonic acid and 0.02 g of di-tert-butyl-4-methylphenol, and stirred at 133°C for 2 h. During the stirring reaction, an inert gas was used for protection and a water separator was used. After the reaction was completed, heating was stopped and the temperature was lowered to obtain an intermediate product 1;

[0038] Q2: 1.78 g of intermediate product 1 was added to a container, followed by 0.028 mL of toluene, 0.03 g of p-toluenesulfonic acid and 0.01 g of hydroquinone. After stirring for 2 h, 0.84 g of acrylic acid was added and the mixture was reacted at 130 °C for 6 h. After the reaction was completed, intermediate product 2 was obtained.

[0039] Q3: 1.5 g of intermediate product 2 was mixed with 0.2 g of propionic acid, and the mixture was stirred at 130°C for 2 h. After the reaction was completed, the mixture was evacuated and cooled to 90°C. 4-methoxyphenol was then added, and the mixture was stirred for 30 min to obtain a polyester compound.

[0040] This embodiment discloses a method for preparing a composite resin, comprising the following steps:

[0041] S1: 0.13 g of paraformaldehyde and 0.5 mL of toluene were added to a container, stirred in an oil bath at 45°C for 45 min, then 1.5 g of 1,1,1-tri-p-hydroxyphenylethane was added, and stirring was continued for 30 min. Then 1.83 g of 5-norbornene-2-methylamine was added to the container, and stirred at 80°C for 12 h. After the reaction was completed, the mixture was first washed with a 1 mol / L NaOH solution, and then washed with deionized water until neutral, rotary evaporated, and vacuum dried to obtain an intermediate product A;

[0042] S2: Add 0.006 g of [1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinylidene]dichloro(phenylmethylene)bis(3-bromopyridinium)ruthenium into a container containing 3 mL of dichloromethane, stir for 45 min, evacuate, and pass nitrogen to obtain a catalyst solution;

[0043] S3: 5.25 g of intermediate product A was added to 5 mL of dichloromethane, followed by the addition of 0.93 g of 2,3-dihydrofuran. After ultrasonic mixing, a mixed solution was obtained. The mixed solution was added to the catalyst solution via a syringe. After stirring at 50°C for 4 h, 0.75 mL of vinyl ethyl ether was added to terminate the reaction, and stirring was continued for 15 min. Subsequently, precipitation, dissolution-precipitation operations were repeated, and vacuum drying was performed at 50°C for 24 h to obtain a composite resin.

[0044] The present embodiment discloses a high-permeability flexible gas sealing material, which is composed of the following components in parts by weight: 25 parts of lime, 11 parts of magnesium oxide, 20 parts of polyester compound, 24 parts of composite resin, 3.5 parts of stabilizer, and 2.5 parts of silane coupling agent.

[0045] This embodiment discloses a method for preparing a high-permeability flexible gas sealing material, comprising the following steps:

[0046] Step (1): mixing lime, magnesium oxide, polyester compound, composite resin and silane coupling agent for 45 minutes to obtain a sealing material premix;

[0047] Step (2): Mix and stir the sealing material premix and the stabilizer for 45 minutes, wherein the stabilizer is obtained by mixing methyl stearate and a 5 wt % polyvinyl alcohol aqueous solution in a dosage ratio of 9 g:12.5 mL, to obtain a high permeability flexible gas sealing material.

[0048] Example 2

[0049] This embodiment discloses a method for preparing a polyester compound, comprising the following steps:

[0050] Q1: 0.5 g of 2-methyl-2-propyl-1,3-propanediol and 3.36 g of 2,4-dihydroxy-3,3-dimethylbutyric acid were mixed and added to a container containing a mechanical stirrer and a thermometer, and mixed at 125°C until molten, followed by adding 0.31 g of p-toluenesulfonic acid and 0.02 g of di-tert-butyl-4-methylphenol, and stirred at 133°C for 2 h. During the stirring reaction, an inert gas was used for protection and a water separator was used. After the reaction was completed, heating was stopped and the temperature was lowered to obtain an intermediate product 1;

[0051] Q2: 1.42 g of intermediate product 1 was added to a container, followed by 0.028 mL of toluene, 0.03 g of p-toluenesulfonic acid and 0.01 g of hydroquinone. After stirring for 2 h, 0.67 g of acrylic acid was added and the mixture was reacted at 130 °C for 6 h. After the reaction was completed, intermediate product 2 was obtained.

[0052] Q3: Mix 1 g of intermediate product 2 with 0.13 g of propionic acid, stir and react at 130°C for 2 h. After the reaction is completed, evacuate the mixture, cool to 90°C, add 4-methoxyphenol, stir and mix for 30 min, and obtain a polyester compound.

[0053] This embodiment discloses a method for preparing a composite resin, comprising the following steps:

[0054] S1: 0.09 g of paraformaldehyde and 0.5 mL of toluene were added to a container, stirred in an oil bath at 45°C for 45 min, then 1 g of 1,1,1-tri-p-hydroxyphenylethane was added, and stirring was continued for 30 min. Then 1.22 g of 5-norbornene-2-methylamine was added to the container, and stirred at 80°C for 12 h. After the reaction was completed, the mixture was first washed with a 1 mol / L NaOH solution, and then washed with deionized water until neutral, rotary evaporated, and vacuum dried to obtain an intermediate product A;

[0055] S2: Add 0.004 g of [1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinylidene]dichloro(phenylmethylene)bis(3-bromopyridinium)ruthenium into a container containing 2 mL of dichloromethane, stir for 45 min, evacuate, and pass nitrogen to obtain a catalyst solution;

[0056] S3: 3.5 g of intermediate product A was added to 5 mL of dichloromethane, followed by the addition of 0.62 g of 2,3-dihydrofuran. After ultrasonic mixing, a mixed solution was obtained. The mixed solution was added to the catalyst solution via a syringe. After stirring at 50°C for 4 h, 0.5 mL of vinyl ethyl ether was added to terminate the reaction, and stirring was continued for 15 min. Subsequently, precipitation, dissolution-precipitation operations were repeated, and vacuum drying was performed at 50°C for 24 h to obtain a composite resin.

[0057] The present embodiment discloses a high-permeability flexible gas sealing material, which is composed of the following components in parts by weight: 20 parts of lime, 10 parts of magnesium oxide, 18 parts of polyester compound, 20 parts of composite resin, 2 parts of stabilizer, and 1 part of silane coupling agent.

[0058] This embodiment discloses a method for preparing a high-permeability flexible gas sealing material, comprising the following steps:

[0059] Step (1): mixing lime, magnesium oxide, polyester compound, composite resin and silane coupling agent for 45 minutes to obtain a sealing material premix;

[0060] Step (2): Mix and stir the sealing material premix and the stabilizer for 45 minutes, wherein the stabilizer is obtained by mixing methyl stearate and a 5 wt% polyvinyl alcohol aqueous solution in a dosage ratio of 8 g:10 mL, to obtain a high permeability flexible gas sealing material.

[0061] Example 3

[0062] This embodiment discloses a method for preparing a polyester compound, comprising the following steps:

[0063] Q1: 1 g of 2-methyl-2-propyl-1,3-propanediol and 6.72 g of 2,4-dihydroxy-3,3-dimethylbutyric acid were mixed and added to a container containing a mechanical stirrer and a thermometer, and mixed at 125°C until molten, followed by adding 0.31 g of p-toluenesulfonic acid and 0.02 g of di-tert-butyl-4-methylphenol, and stirred at 133°C for 2 h. During the stirring reaction, an inert gas was used for protection and a water separator was used. After the reaction was completed, heating was stopped and the temperature was lowered to obtain an intermediate product 1;

[0064] Q2: 2.13 g of intermediate product 1 was added to a container, followed by 0.028 mL of toluene, 0.03 g of p-toluenesulfonic acid and 0.01 g of hydroquinone. After stirring for 2 h, 1 g of acrylic acid was added and the mixture was reacted at 130 °C for 6 h. After the reaction was completed, intermediate product 2 was obtained.

[0065] Q3: Mix 2 g of intermediate product 2 with 0.26 g of propionic acid, stir and react at 130°C for 2 h. After the reaction is completed, evacuate the mixture, cool to 90°C, add 4-methoxyphenol, stir and mix for 30 min, and obtain a polyester compound.

[0066] This embodiment discloses a method for preparing a composite resin, comprising the following steps:

[0067] S1: 0.18 g of paraformaldehyde and 0.5 mL of toluene were added to a container, stirred in an oil bath at 45°C for 45 min, then 2 g of 1,1,1-tri-p-hydroxyphenylethane was added, and stirring was continued for 30 min. Then 2.44 g of 5-norbornene-2-methylamine was added to the container, and stirred at 80°C for 12 h. After the reaction was completed, the mixture was first washed with a 1 mol / L NaOH solution, and then washed with deionized water until neutral, rotary evaporated, and vacuum dried to obtain an intermediate product A;

[0068] S2: Add 0.008 g of [1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinylidene]dichloro(phenylmethylene)bis(3-bromopyridine)ruthenium to a container containing 4 mL of dichloromethane, stir for 45 min, evacuate, and pass nitrogen to obtain a catalyst solution;

[0069] S3: 7 g of intermediate product A was added to 5 mL of dichloromethane, followed by 1.24 g of 2,3-dihydrofuran. After ultrasonic mixing, a mixed solution was obtained. The mixed solution was added to the catalyst solution via a syringe. After stirring at 50°C for 4 h, 1 mL of vinyl ethyl ether was added to terminate the reaction, and stirring was continued for 15 min. Subsequently, precipitation, dissolution-precipitation operations were repeated, and vacuum drying was performed at 50°C for 24 h to obtain a composite resin.

[0070] The present embodiment discloses a high-permeability flexible gas sealing material, which is composed of the following components in parts by weight: 30 parts of lime, 12 parts of magnesium oxide, 22 parts of polyester compound, 28 parts of composite resin, 5 parts of stabilizer, and 2 parts of silane coupling agent.

[0071] This embodiment discloses a method for preparing a high-permeability flexible gas sealing material, comprising the following steps:

[0072] Step (1): mixing lime, magnesium oxide, polyester compound, composite resin and silane coupling agent for 45 minutes to obtain a sealing material premix;

[0073] Step (2): Mix and stir the sealing material premix and the stabilizer for 45 minutes, wherein the stabilizer is obtained by mixing methyl stearate and a 5 wt % polyvinyl alcohol aqueous solution in a dosage ratio of 10 g:15 mL, to obtain a high permeability flexible gas sealing material.

[0074] Example 4

[0075] This embodiment discloses a method for preparing a polyester compound, comprising the following steps:

[0076] Q1: 0.6 g of 2-methyl-2-propyl-1,3-propanediol and 4.5 g of 2,4-dihydroxy-3,3-dimethylbutyric acid were mixed and added to a container containing a mechanical stirrer and a thermometer, and mixed at 125°C until molten, followed by adding 0.31 g of p-toluenesulfonic acid and 0.02 g of di-tert-butyl-4-methylphenol, and stirred at 133°C for 2 h. During the stirring reaction, an inert gas was used for protection and a water separator was used. After the reaction was completed, heating was stopped and the temperature was lowered to obtain an intermediate product 1;

[0077] Q2: 1.6 g of intermediate product 1 was added to a container, followed by 0.028 mL of toluene, 0.03 g of p-toluenesulfonic acid and 0.01 g of hydroquinone. After stirring for 2 h, 0.92 g of acrylic acid was added and reacted at 130 °C for 6 h. After the reaction was completed, intermediate product 2 was obtained.

[0078] Q3: 1.2 g of intermediate product 2 was mixed with 0.15 g of propionic acid, and the mixture was stirred at 130°C for 2 h. After the reaction was completed, the mixture was evacuated and cooled to 90°C. 4-methoxyphenol was then added, and the mixture was stirred for 30 min to obtain a polyester compound.

[0079] This embodiment discloses a method for preparing a composite resin, comprising the following steps:

[0080] S1: 0.11 g of paraformaldehyde and 0.5 mL of toluene were added to a container, stirred in an oil bath at 45°C for 45 min, then 1.2 g of 1,1,1-tri-p-hydroxyphenylethane was added, and stirring was continued for 30 min. Then 1.53 g of 5-norbornene-2-methylamine was added to the container, and stirred at 80°C for 12 h. After the reaction was completed, the mixture was first washed with a 1 mol / L NaOH solution, and then washed with deionized water until neutral, rotary evaporated, and vacuum dried to obtain an intermediate product A;

[0081] S2: Add 0.005 g of [1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinyl]dichloro(phenylmethylene)bis(3-bromopyridinium)ruthenium to a container containing 2.5 mL of dichloromethane, stir for 45 min, evacuate, and pass nitrogen to obtain a catalyst solution;

[0082] S3: 4.38 g of intermediate product A was added to 5 mL of dichloromethane, followed by the addition of 1.09 g of 2,3-dihydrofuran. After ultrasonic mixing, a mixed solution was obtained. The mixed solution was added to the catalyst solution via a syringe. After stirring at 50°C for 4 h, 0.6 mL of vinyl ethyl ether was added to terminate the reaction, and stirring was continued for 15 min. Subsequently, precipitation, dissolution-precipitation operations were repeated, and vacuum drying was performed at 50°C for 24 h to obtain a composite resin.

[0083] The present embodiment discloses a high-permeability flexible gas sealing material, which is composed of the following components in parts by weight: 28 parts of lime, 10.5 parts of magnesium oxide, 19 parts of polyester compound, 22 parts of composite resin, 3 parts of stabilizer, and 3 parts of silane coupling agent.

[0084] This embodiment discloses a method for preparing a high-permeability flexible gas sealing material, comprising the following steps:

[0085] Step (1): mixing lime, magnesium oxide, polyester compound, composite resin and silane coupling agent for 45 minutes to obtain a sealing material premix;

[0086] Step (2): Mix and stir the sealing material premix and the stabilizer for 45 minutes, wherein the stabilizer is obtained by mixing methyl stearate and a 5 wt % polyvinyl alcohol aqueous solution in a dosage ratio of 8.5 g:11 mL, to obtain a high permeability flexible gas sealing material.

[0087] Example 5

[0088] This embodiment discloses a method for preparing a polyester compound, comprising the following steps:

[0089] Q1: 0.9 g of 2-methyl-2-propyl-1,3-propanediol and 6.13 g of 2,4-dihydroxy-3,3-dimethylbutyric acid were mixed and added to a container containing a mechanical stirrer and a thermometer, and mixed at 125°C until molten, and then 0.31 g of p-toluenesulfonic acid and 0.02 g of di-tert-butyl-4-methylphenol were added, and stirred at 133°C for 2 h. During the stirring reaction, inert gas was used for protection and a water separator was used. After the reaction was completed, heating was stopped and the temperature was lowered to obtain intermediate 1;

[0090] Q2: 1.96 g of intermediate product 1 was added to a container, followed by 0.028 mL of toluene, 0.03 g of p-toluenesulfonic acid and 0.01 g of hydroquinone. After stirring for 2 h, 0.76 g of acrylic acid was added and reacted at 130 °C for 6 h. After the reaction was completed, intermediate product 2 was obtained.

[0091] Q3: 1.7 g of intermediate product 2 was mixed with 0.21 g of propionic acid, and the mixture was stirred at 130°C for 2 h. After the reaction was completed, the mixture was evacuated and cooled to 90°C. 4-methoxyphenol was then added, and the mixture was stirred for 30 min to obtain a polyester compound.

[0092] This embodiment discloses a method for preparing a composite resin, comprising the following steps:

[0093] S1: 0.15 g of paraformaldehyde and 0.5 mL of toluene were added to a container, stirred in an oil bath at 45° C. for 45 min, then 1.7 g of 1,1,1-tri-p-hydroxyphenylethane was added, and stirring was continued for 30 min. Then 2.14 g of 5-norbornene-2-methylamine was added to the container, and stirred at 80° C. for 12 h. After the reaction was completed, the mixture was first washed with a 1 mol / L NaOH solution, and then washed with deionized water until neutral, rotary evaporated, and vacuum dried to obtain an intermediate product A;

[0094] S2: Add 0.007 g of [1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinylidene]dichloro(phenylmethylene)bis(3-bromopyridine)ruthenium into a container containing 3.5 mL of dichloromethane, stir for 45 min, evacuate, and pass nitrogen to obtain a catalyst solution;

[0095] S3: 6.13 g of intermediate product A was added to 5 mL of dichloromethane, followed by 0.78 g of 2,3-dihydrofuran. After ultrasonic mixing, a mixed solution was obtained. The mixed solution was added to the catalyst solution via a syringe. After stirring at 50°C for 4 h, 0.7 mL of vinyl ethyl ether was added to terminate the reaction, and stirring was continued for 15 min. Subsequently, precipitation, dissolution-precipitation operations were repeated, and vacuum drying was performed at 50°C for 24 h to obtain a composite resin.

[0096] The present embodiment discloses a high-permeability flexible gas sealing material, which is composed of the following components in parts by weight: 22 parts of lime, 11.5 parts of magnesium oxide, 21 parts of polyester compound, 26 parts of composite resin, 4 parts of stabilizer, and 4 parts of silane coupling agent.

[0097] This embodiment discloses a method for preparing a high-permeability flexible gas sealing material, comprising the following steps:

[0098] Step (1): mixing lime, magnesium oxide, polyester compound, composite resin and silane coupling agent for 45 minutes to obtain a sealing material premix;

[0099] Step (2): Mix and stir the sealing material premix and the stabilizer for 45 minutes, wherein the stabilizer is obtained by mixing methyl stearate and a 5 wt % polyvinyl alcohol aqueous solution in a dosage ratio of 9.5 g:13 mL, to obtain a high permeability flexible gas sealing material.

[0100] Comparative Example 1

[0101] Comparative Example 1 Compared with Example 1, in the preparation process of the polyester compound in Comparative Example 1, 2-methyl-2-propyl-1,3-propanediol was not added, and other conditions remained unchanged.

[0102] Comparative Example 2

[0103] Comparative Example 2 Compared with Example 1, in the preparation process of the polyester compound in Comparative Example 2, no acrylic acid is added, and other conditions remain unchanged.

[0104] Comparative Example 3

[0105] Comparative Example 3 Compared with Example 1, in the preparation process of the composite resin in Comparative Example 3, 1,1,1-tri-p-hydroxyphenylethane was not added, and other conditions remained unchanged.

[0106] Comparative Example 4

[0107] Comparative Example 4 Compared with Example 1, in the preparation process of the composite resin in Comparative Example 4, 5-norbornene-2-methylamine was not added, and other conditions remained unchanged.

[0108] Comparative Example 5

[0109] Comparative Example 5 Compared with Example 1, in the preparation process of the high-permeability flexible gas sealing material in Comparative Example 5, no polyester compound is added, and other conditions remain unchanged.

[0110] Comparative Example 6

[0111] Comparative Example 6 Compared with Example 1, in the preparation process of the high-permeability flexible gas sealing material in Comparative Example 6, no composite resin is added, and other conditions remain unchanged.

[0112] The samples prepared according to Examples 1-5 and Comparative Examples 1-6 were added to a stirring barrel. After electric stirring for 5 minutes, the stirring barrel was slightly shaken and slowly injected into the mold. The mold was coated with a release agent in advance. The mold containing the sample was then placed in a constant temperature and pressure standard curing box at a temperature of 20-22°C and a humidity of 97%. After standing for 12 hours, the mold was demolded to obtain a solid sample of the packaging material. The dimensional stability of the solid sample was tested according to GB / T 8811-2008, the anti-corrosion performance of the sample was tested according to GB / T 28416-2012, and the compressive strength (Σc) before and after the test was measured. According to Σc change rate = [(Σc before - Σc after) / Σc before] × 100%, the bending performance of the sample was tested according to GB / T 8812.1-2007. The test results are shown in Table 1:

[0113] Table 1

[0114]

[0115] It can be seen from the test results in Table 1 that the sealing materials prepared in Examples 1-5 of the present invention have excellent stability, corrosion resistance and flexibility. By comparing Comparative Example 1 with Examples 1-5, it can be seen that the addition of 2-methyl-2-propyl-1,3-propanediol can make the obtained sealing material have excellent flexibility and stability; by comparing Comparative Example 2 with Examples 1-5, it can be seen that the addition of acrylic acid can make the obtained sealing material have excellent flexibility and stability; by comparing Comparative Example 3 with Examples 1-5, it can be seen that the addition of 1,1,1-tri-p-hydroxyphenylethane can make the obtained sealing material have excellent corrosion resistance and stability; by comparing Comparative Example 4 with Examples 1-5, it can be seen that the addition of 5-norbornene-2-methylamine can make the obtained sealing material have excellent corrosion resistance and stability; by comparing Comparative Example 5 with Examples 1-5, it can be seen that the addition of polyester compounds can make the obtained sealing material have excellent flexibility and stability; by comparing Comparative Example 6 with Examples 1-5, it can be seen that the addition of composite resin can make the obtained sealing material have excellent corrosion resistance and stability.

[0116] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0117] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. High permeability flexible gas sealing material, characterized in that: The invention is composed of the following components in parts by weight: 20-30 parts of lime, 10-12 parts of magnesium oxide, 18-22 parts of polyester compound, 20-28 parts of composite resin, 2-5 parts of stabilizer, and 1-4 parts of silane coupling agent, wherein the polyester compound is prepared from 2-methyl-2-propyl-1,3-propanediol, 2,4-dihydroxy-3,3-dimethylbutyric acid and acrylic acid, and the composite resin is prepared from 1,1,1-tri-p-hydroxyphenylethane, 5-norbornene-2-methylamine and 2,3-dihydrofuran; The preparation method of the polyester compound comprises the following steps: Q1: 2-methyl-2-propyl-1,3-propanediol and 2,4-dihydroxy-3,3-dimethylbutyric acid are mixed and added to a container, heated and mixed until molten, and then p-toluenesulfonic acid and di-tert-butyl-4-methylphenol are added, and the temperature is raised and stirred to react. After the reaction is completed, the heating is stopped and the temperature is lowered to obtain an intermediate product 1; Q2: Add intermediate product 1 to a container, then add toluene, p-toluenesulfonic acid and hydroquinone, stir evenly, add acrylic acid, heat and react, and after the reaction is completed, obtain intermediate product 2; Q3: The intermediate product 2 is mixed with propionic acid, heated and stirred for reaction, and after the reaction is completed, vacuum is evacuated, cooled, and then 4-methoxyphenol is added, and stirred and mixed to obtain a polyester compound; The preparation method of the composite resin comprises the following steps: S1: Add paraformaldehyde and toluene into a container, heat and stir in an oil bath, then add 1,1,1-tri-p-hydroxyphenylethane, continue stirring, then add 5-norbornene-2-methylamine into the container, heat and stir to react, after the reaction is completed, wash, rotary evaporate, and vacuum dry to obtain intermediate product A; S2: Add [1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinyl]dichloro(phenylmethylene)bis(3-bromopyridinium)ruthenium into a container containing dichloromethane, stir to dissolve, evacuate, and pass nitrogen to obtain a catalyst solution; S3: The intermediate product A is added to dichloromethane, followed by 2,3-dihydrofuran, and ultrasonically mixed to obtain a mixed solution, which is added to the catalyst solution via a syringe. After heating and stirring, ethyl vinyl ether is added to terminate the reaction, and stirring is continued. Subsequently, precipitation, dissolution-precipitation operations are repeated, and vacuum drying is performed to obtain a composite resin.

2. The high permeability flexible gas sealing material according to claim 1, characterized in that: In Q1, the molar ratio of 2-methyl-2-propyl-1,3-propanediol and 2,4-dihydroxy-3,3-dimethylbutyric acid is (1-2): (6-12), the container contains a mechanical stirrer and a thermometer, the heating and mixing temperature is 125-130°C, the heating and stirring reaction temperature is 130-135°C, during the stirring reaction, inert gas is used for protection and a water separator is used, and the reaction time is 2-4h; in Q2, the molar ratio of the intermediate product 1 and acrylic acid is (1-1.5): (6-9), the stirring time is 1-2h, the heating and reaction temperature is 120-130°C, and the reaction time is 6-8h; in Q3, the molar ratio of the intermediate product 2 and propionic acid is (1-2): (2-4), the heating and stirring temperature is 120-130°C, the reaction time is 1-2h, and the mixture is cooled to 90-95°C and the stirring and mixing time is 20-30min.

3. The high permeability flexible gas sealing material according to claim 1, characterized in that: In the S1, the molar ratio of paraformaldehyde, 1,1,1-tri-p-hydroxyphenylethane and 5-norbornene-2-methylamine is (1-2): (3-6): (9-18), the oil bath heating temperature is 40-45°C, the stirring time is 30-45min, the continued stirring time is 30-45min, the heating and stirring reaction temperature is 70-80°C, the stirring reaction time is 12-15h, and the product is first washed with 1mol / L NaOH solution and then washed with deionized water until neutral.

4. The high permeability flexible gas sealing material according to claim 1, characterized in that: In S2, the dosage ratio of [1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinyl]dichloro(phenylmethylene)bis(3-bromopyridine)ruthenium and dichloromethane is (0.004-0.008) g: (2-4) mL, and the stirring time is 30-45 min.

5. The high permeability flexible gas sealing material according to claim 1, characterized in that: In the S3, the usage ratio of the intermediate product A, 2,3-dihydrofuran and vinyl ethyl ether is (3.5-7) g: (0.62-1.24) g: (0.5-1) mL, the heating and stirring temperature is 40-50° C., the stirring time is 2-4 h, the continued stirring time is 10-15 min, and the vacuum drying temperature is 50-60° C. for 20-24 h.

6. The high permeability flexible gas sealing material according to claim 1, characterized in that: The stabilizer is obtained by mixing methyl stearate and polyvinyl alcohol aqueous solution, wherein the mass fraction of the polyvinyl alcohol aqueous solution is 5wt%-10wt%, and the dosage ratio of methyl stearate to polyvinyl alcohol aqueous solution is (8-10)g:(10-15)mL.

7. The method for preparing a high-permeability flexible gas sealing material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step (1): mixing and stirring lime, magnesium oxide, polyester compound, composite resin and silane coupling agent to obtain a sealing material premix; Step (2): Mix and stir the sealing material premix and the stabilizer to obtain a high-permeability flexible gas sealing material.

8. The method for preparing a high-permeability flexible gas sealing material according to claim 7, characterized in that: In the step (1), the mixing and stirring time is 30-45 minutes; in the step (2), the mixing and stirring time is 30-45 minutes.

Citation Information

Patent Citations

  • A flexible gas sealing material based on waste incineration fly ash and its preparation method

    CN113248197B

  • Polyester-based resin composition, method for producing same, and molding using resin composition

    CN104159970A

  • Garbage incineration fly ash-based flexible gas hole sealing material and preparation method thereof

    CN113248197A